Study of the types and characteristics of geological hazards in reefs of Nansha Waters, South China Sea. Issue 1 (January 2020) - Guo, Lei; Qian, Jing; Lei, Chengbin; Cai, Yihuang; Zhao, Hongjuan
Abstract: Reports of the 19th National Congress of the Communist Party of China identifies that the construction of islands and reefs in South China Sea (SCS) has been actively promoted. It is of great practical significance to study the types and characteristics of geological hazards in Nansha Islands and reefs, and it is the precondition and guarantees to carry out the construction of islands and reefs. At present, the research on marine geological hazards in China focuses on oil and gas enrichment areas such as Bohai bay, southern Yellow Sea and Northern of South China Sea, and there is little research on southern of South China Sea, especially Nansha Reefs. On the basis of collecting and sorting out previous research achievements, combining with existing geological and geophysical data and drilling data, his paper focuses on analysing two single-channel seismic profiles N01 and N02 collected by "Shiyan 2" of South China Sea institute of Chinese academy of sciences in Nansha Islands and reefs in 2013, and studies the types and characteristics of geological hazards in this area. The study shows that the whole Nansha block belongs to areas with weak seismic activity, most of the faults in the island reef area are weak and micro-active, and the volcanic activity in the island reef area is weak, and the coral reef growth rate is fast, which can be suitable for all kinds of engineering construction projects.